1992
DOI: 10.1111/j.1365-313x.1992.00385.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure and growth of infection threads in the legume symbiosis with Rhizobium leguminosarum

Abstract: Summary Specific antibodies and enzyme–gold probes were used to study the structure and development of infection threads in nodules induced by Rhizobium leguminosarum on the roots of Vicia, Pisum and Phaseolus. In Pisum nodules, the tubular infection thread wall contains polysaccharides antigenically similar to those of the cell wall, including cellulose, xyloglucan, methyl‐esterified pectin and non‐esterified pectin, but none of these wall components is present around the infection droplet structures from whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
7

Year Published

1995
1995
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(82 citation statements)
references
References 29 publications
1
74
0
7
Order By: Relevance
“…As a very low O # concentration is necessary for the expression and function of nitrogenase (Gallon, 1992), it is essential that an O # -diffusion barrier be formed in young nodules before N # fixation can occur within them (Sheehy & Thornley, 1988) potential role of the MAC236\MAC265 glycoprotein in the formation of such a barrier has previously been shown in terrestrially grown lupin nodules by James et al (1997), and the pattern of localization shown by the present study suggests that it may have a similar function in Lotus nodules, even under the low O # concentrations created by flooding. Although large infection threads have been recently reported by Szczyglowski et al (1998) in young nodules of L. japonicus, most previous studies of the development of nodules on Lotus (Pankhurst et al, 1979 ;Vance et al, 1982 ;Wood et al, 1985) have suggested that infection threads and infection droplets are relatively scarce and fairly small structures, at least in comparison to indeterminate nodules such as those found on pea (Newcomb et al, 1979 ;Rae et al, 1992). However, the present study has shown that, for a short period during nodule development, there is massive proliferation of quite large infection threads within L. uliginosus, with many of them releasing MAC236-labelled material into host cells more or less simultaneously, and hence producing the dense immunolabelling shown in Fig.…”
Section: Nodule Development and Expression Of Glycoproteinsmentioning
confidence: 94%
See 3 more Smart Citations
“…As a very low O # concentration is necessary for the expression and function of nitrogenase (Gallon, 1992), it is essential that an O # -diffusion barrier be formed in young nodules before N # fixation can occur within them (Sheehy & Thornley, 1988) potential role of the MAC236\MAC265 glycoprotein in the formation of such a barrier has previously been shown in terrestrially grown lupin nodules by James et al (1997), and the pattern of localization shown by the present study suggests that it may have a similar function in Lotus nodules, even under the low O # concentrations created by flooding. Although large infection threads have been recently reported by Szczyglowski et al (1998) in young nodules of L. japonicus, most previous studies of the development of nodules on Lotus (Pankhurst et al, 1979 ;Vance et al, 1982 ;Wood et al, 1985) have suggested that infection threads and infection droplets are relatively scarce and fairly small structures, at least in comparison to indeterminate nodules such as those found on pea (Newcomb et al, 1979 ;Rae et al, 1992). However, the present study has shown that, for a short period during nodule development, there is massive proliferation of quite large infection threads within L. uliginosus, with many of them releasing MAC236-labelled material into host cells more or less simultaneously, and hence producing the dense immunolabelling shown in Fig.…”
Section: Nodule Development and Expression Of Glycoproteinsmentioning
confidence: 94%
“…3a-d. The amounts of MAC236-labelled material seen in the meristematic L. uliginosus nodules are reminiscent of the dense labelling (by MAC236 and\or MAC265) of infection threads and\or infection droplets observed in the invasion zone of indeterminate nodules on pea (VandenBosch et al, 1989 ;Rae et al, 1992) and Neptunia (James et al, 1992b), rather than the rather sparse labelling seen in other determinate nodules, such as those on soybean (VandenBosch et al, 1989), P. vulgaris (Rae et al, 1992) and Vigna subterranea (Gueye et al, 1998). In Lotus, the MAC236-labelled material released from infection threads along with the rhizobia probably corresponded to the material observed by Vance et al (1982), and Wood et al (1985), and which Vance et al (1982) considered to be at least partly composed of polysaccharide.…”
Section: Nodule Development and Expression Of Glycoproteinsmentioning
confidence: 96%
See 2 more Smart Citations
“…The interfacial membrane in AMs seems to retain synthetic activity as indicated by the deposition of /?-l,4 glucans around the fungus (see IV.2), whereas the peribacteroid membrane surrounding rhizobia ceases its synthetic activity and no glucans are found at the interface with the bacterium (Rae, Bonfante & Brewin, 1992).…”
Section: Development Of An Interface Is a Recurrent Feature M Symbiotmentioning
confidence: 99%